Socio-demographic and environmental determinants of attention deficit hyperactivity disorder in primary school children in Ikot Ekpene, Nigeria - Hogan, Ekemini Joseph; Akpan, Mkpouto Udeme; Ijezie, Echey; Edem, Kevin Bassey (International Journal of Contemporary Pediatrics, 2021)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common neuro-behavioural disorders of childhood. Environmental influences have been reported to be important in its aetiopathogenesis. There is a paucity of publications assessing the socio-demographic and environmental determinants of ADHD in Sub Saharan Africa. The aim was to determine the socio-demographic and environmental determinants of ADHD in primary school children in Ikot Ekpene, Nigeria. Methods: Vanderbilt ADHD diagnostic teacher rating scale for ADHD was administered on 1174 pupils aged 6-12 years drawn from twelve primary schools in Ikot-Ekpene, Akwa-Ibom State, Nigeria. Parents of the selected pupils completed a proforma on their socio-demographics and environmental factors. Results: The mean age of the study population was 9.32 years with a male preponderance. ADHD was significantly associated with lower socio-economic status, being a product of multiple gestations, having parents with financial difficulty during the first few years of child’s life among others. Conclusions: ADHD is associated with common socio-demographic and environmental risk factors. Some of these factors such as low income and low socio-economic status are modifiable. Poverty alleviation, job security and empowerment of parents of children living in resource-poor settings is critical to reducing the prevalence of ADHD.